Assessment of Health Problems for the Elderly at the Nursing Home in Baghdad city - Abdul Mohsin, mohammed; AL. Janabi, Nahida; Al - Naqeeb, Abdul Khaleq (Iraqi National Journal of Nursing Specialties, 2012)
Objective: Assessment of health problems and identify demographical information to elderly. Methodology:it is a descriptive study, data were collected by the researchers depended on the direct interview with theelderly by using the study instrument (questionnaire) as well as review the records of the geriatric.Results: The majority of study sample (66%) were males and (24.3%) were within age group (70-74) years,(44.7%) were widows, and (41.7%) did not read and write. This study applied the international classificationof diseases(short-table) in (11) items, which stated that most of the elderly were complaining fromhealth problems: debility of hearing (80.65%), eczema or allergies (69.35%), debility of vision (66.92%), difficultybreathing (65.56%), loss of teeth (56.7%), chronic arthritis (54.55%), chronic headache (51.75%), anemia(51.56%), chronic constipation (46.36%), heart failure (30.43%), and retention of urine (30.19%).Recommendations: There must be a doctor with diseases of ageing presented at Nursinghome and nursing staff commensurate with the number of elderly.